(untitled) (TAMADDUN NURI JURNALI, 2024)
This article describes the theoretical foundations of the development of innovative professional competence of primary education students. The formation of this competence is one of the urgent tasks in modern educational processes and is important in increasing the effectiveness of pedagogical activity. The article analyzes the definition, importance and application of innovative methods in education, as well as the psychological and pedagogical basis of this process. From a scientific point of view, what kind of pedagogical conditions are necessary for students to acquire the skills of effective use of innovative teaching methods and technologies.